THE ANALYSIS ON THE TRANSLATION OF FROZEN MOVIEâ€™S SOUNTRACT - Priska Meilasari (Universitas Katolik Widya Mandala Surabaya, 2017)
This research aimed at finding the translation features of song lyric translation and judging the singability level of the translated song. The research was descriptive qualitative in nature. The data to be analyzed was taken from the soundtrack of Frozen Movie by Disney entitled â€œLet It Goâ€. This soundtrack was chosen because of its Â popularity amongst the society. Besides, this song had been translated into Indonesia both for dubbing and subtitling. Here, the translated version taken as the data was the one which was applied in dubbing. The result of the research showed that mostly used translation feature was the use of rhyme. Unfortunately, the rhyme of the original song were mostly translated into non-rhyming words. The other features that were also contributive were omission of words and use of paraphrase respectively. The analysis on the singability level was also showed an interesting result. The prosodic match reached the high level while the poetic match reached the middle level. Â Keywords: song lyric, translation, dubbing